Antiretroviral therapy in Malaysia: identifying barriers to universal access - Kamarulzaman, A. (2009)
Despite a good public healthcare infrastructure and greater availability of antiretroviral drugs in Malaysia since 2005, the number of HIV-infected patients receiving treatment remains disproportionately small. Barriers to greater access include a lack of trained human resources to deliver antiretroviral therapy (ART) in a highly individualized and specialized model and, until recently, a lack of treatment for substance abuse in a predominantly injecting drug-use epidemic. However, one of the biggest barriers, and perhaps the most challenging to overcome, is the stigma and discrimination towards HIV-infected people, especially injecting drug users, which prevented many from accessing treatment and care. Increasing and improved access to ART for HIV-infected patients will entail a multipronged strategy that includes the decentralization of clinical care, increased and ongoing training of healthcare workers and support staff, and a comprehensive and intensive effort to reduce stigma and discrimination. Creation of an enabling environment through public education and a well-trained and nonprejudicial healthcare work force, coupled with policy and legal reforms, are essential in ensuring a greater and sustainable access to ART for all.